2019
DOI: 10.3390/molecules24162933
|View full text |Cite
|
Sign up to set email alerts
|

How Far Can One Push the Noble Gases Towards Bonding?: A Personal Account

Abstract: Noble gases (Ngs) are the least reactive elements in the periodic table towards chemical bond formation when compared with other elements because of their completely filled valence electronic configuration. Very often, extreme conditions like low temperatures, high pressures and very reactive reagents are required for them to form meaningful chemical bonds with other elements. In this personal account, we summarize our works to date on Ng complexes where we attempted to theoretically predict viable Ng complexe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 145 publications
(154 reference statements)
1
29
0
Order By: Relevance
“…Previously, by heating fullerenes at 650°C under 3,000 atmosphere, helium (Saunders et al, 1993 ), neon (Saunders et al, 1993 ), argon (DiCamillo et al, 1996 ), krypton (Yamamoto et al, 1999 ), and xenon (Syamala et al, 2002 ) noble gas atoms were experimentally introduced into the fullerene cage. This experimental realization of fullerene encapsulation demonstrates the feasibility, and there were reports of experimental realization of noble gas dimers encapsulation in fulerenes (Saunders et al, 1996 ; Laskin et al, 1998 ; Peres et al, 2001 ; Popov et al, 2013 ; Saha et al, 2019 ). Also, earlier, Krapp and Frenking performed a computational study on Ng 2 @C 60 (Ng = He, Ne, Ar, Kr, and Xe) systems from the bonding perspective and concluded that He 2 @C 60 and Ne 2 @C 60 were weakly bonded van der Waals complexes (Krapp and Frenking, 2007 ).…”
Section: Introductionsupporting
confidence: 56%
“…Previously, by heating fullerenes at 650°C under 3,000 atmosphere, helium (Saunders et al, 1993 ), neon (Saunders et al, 1993 ), argon (DiCamillo et al, 1996 ), krypton (Yamamoto et al, 1999 ), and xenon (Syamala et al, 2002 ) noble gas atoms were experimentally introduced into the fullerene cage. This experimental realization of fullerene encapsulation demonstrates the feasibility, and there were reports of experimental realization of noble gas dimers encapsulation in fulerenes (Saunders et al, 1996 ; Laskin et al, 1998 ; Peres et al, 2001 ; Popov et al, 2013 ; Saha et al, 2019 ). Also, earlier, Krapp and Frenking performed a computational study on Ng 2 @C 60 (Ng = He, Ne, Ar, Kr, and Xe) systems from the bonding perspective and concluded that He 2 @C 60 and Ne 2 @C 60 were weakly bonded van der Waals complexes (Krapp and Frenking, 2007 ).…”
Section: Introductionsupporting
confidence: 56%
“…Strongly electronegative ligands, such as O and F atoms, have been found to be able to form neutral, covalently bound structures with Ar, Kr, and Xe, with the latter in particular displaying a rich chemical nature, but neutral compounds containing bound He and Ne have generally not been achieved [1][2][3]. Exotic exceptions to this are compounds formed under extreme pressures [4] or by trapping noble gases in molecular cages [3,5,6]. However, molecular ions containing covalently bound rare gases, including He and Ne, can be readily formed and have been studied since the discovery of the HeH + ion nearly a century ago [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, significant progress has been made in noble-gas chemistry during the past 20 years. Besides noble-gas hydrides (Khriachtchev et al, 2009), noble gas-noble metal complexes have been studied for their thermodynamic and kinetic stabilities in theory (Jana et al, 2017(Jana et al, , 2018aPan et al, 2019;Saha et al, 2019). Experimentally, about 30 noble-gas hydrides had been identified by the beginning of 1995 (Pettersson et al, 1995;Räsänen et al, 2000;Lundell et al, 2002;Feldman et al, 2003;Khriachtchev et al, 2003Khriachtchev et al, , 2009Duarte and Khriachtchev, 2017).…”
Section: Introductionmentioning
confidence: 99%